Glycosylation Governs the Binding of Antipeptide Antibodies to Regions of Hypervariable Amino Acid Sequence within Recombinant gp120 of Human Immunodeficiency Virus Type 1 - Davis, David; Stephens, D. Michael; Willers, Christine; Lachmann, Peter J. (Journal of General Virology, 1990)
Antibodies raised to an overlapping series of peptides following the amino acid sequence of the external envelope glycoprotein (gpl20) of human immunodeficiency virus type 1 (HIV-1) recognize eight regions in recombinant gpl20 molecules. If the recombinant molecules are glycosylated, three of these regions show a reduced capacity to bind antibody. Of the other five regions, two are strain-specific and carbohydrate restricts antibody binding to their N-terminal flanks, and three can be recognized by antibodies in recombinant gpl20 from an unrelated strain of HIV-1. Antibodies in sera from HIV-l-infected patients bind at high levels to peptides from five regions of gpl20. Of these regions, two coincide with those recognized by antibodies raised to peptides. Four of the five epitopes recognized by the rat antipeptide sera whose ability to bind antibody is influenced most by glycosylation, and three of the five regions which induce high levels of antibodies in patients’ sera, contain putative glycosylation sites which are variable between strains of HIV-1. Such sites flank the putative neutralization and CD4-binding regions of gpl20. It is suggested that changes in the number and position of carbohydrate moieties following mutation can alternately mask and reveal epitopes. Masking an epitope can render a virus resistant to neutralization, whereas virus which binds antibody without being neutralized is able to gain entry to cells bearing antibody and complement receptors. Changes in the glycosylation pattern of gpl20 may therefore contribute to the control of HIV-1 spread within its host.